Analisis Penggunaan Alat Mesin Pertanian Berbasis Traktor Tangan pada Kegiatan Perawatan Budidaya Tebu - Deddy Purwantoro; Trikuntari Dianpratiwi; Sri Markumningsih (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Java contributes 63.7% of national sugar production, in which 55.6% is produced by the farmer from 312,973 ha of sugarcane area (65.6% of Indonesia’s cane crop area). Farm labor in Java was very limited in the past two decades, so was needed mechanization. Howeveer, the size of agricultural machines were not accordance with the size of land, the limited of spares, and was not optimally managed. This research aimed to calculate operational cost of farm machinery (hand tractor) on the cane cultivation activities up to 6-month cane growth period. This study was carried out at Comal, Center of Java at alluvial land 8 mdpl and at Pasuruan, East Java at alluvial 10 mdpl. From each location, 2 plots of 0.1 ha were observed. The treatments were manual and machine cultivation with 3 replications. The observed agrotechnical parameters were the bud emergence, number of stalk, clump, stalk height and diameter, and operational cost of using machinery. The agrotechnical result using t-test (95% confidence rate) showed no significance among treatments. Other results revealed that using machinery for fertilizing, soil heaping up, and soil moving (gulud) in Pasuruan can substitute manual daily worker (HOK) for 6 HOK, 12 HOK and 20 HOK, respectively, using tractor by 7 hours/day. Meanwhile in Comal, using machinery for fertilizing, soil heaping up, and soil hilling up (gulud) can substitute manual daily worker (HOK) for 9 HOK, 16 HOK, and 20 HOK, respectively. The cost analysis indicated the 35.54% reduction of using machinery compared to the manual expense. This study revealed that the machinery could substitute the manual worker for cane cultivation.